Ruptured Hepatocellular Carcinoma: What Do Interventional Radiologists Need to Know? - Yan, Jingxin; Li, Ting; Deng, Manjun; Fan, Haining (Frontiers in Oncology, 2022)
Rupture of HCC (rHCC) is a life-threatening complication of hepatocellular carcinoma (HCC) and rHCC may lead to high rate of peritoneal dissemination and impact survival negatively. The treatments for rHCC mainly include emergency surgery, interventional therapies, and palliative treatment. However, the management of rHCC should be carefully evaluated. For patients with severe bleeding, who are not tolerant to open operation, quick hemostatic methods such as rupture tissue ablation, and TAE/TACE can be performed. We described clinical presentation, prognosis, complication, interventional management, and current evidence of the rHCC from the perspective of interventional radiologist. Overall, our review summarized that interventional therapies are optimal for most patients with rHCC to achieve hemostasis, even in some patients with Child-Pugh C. Besides, TAE/TACE followed by staged hepatectomy a beneficial treatment for rHCC according to current clinical evidence. TAE/TACE is the first choice for most patients with rHCC, and appropriate interventional treatment may provide staged surgery opportunities for those who are not tolerant to emergency surgery and reach an ideal prognosis.